Avoidable hospitalizations of the elderly in the state of Ceará: a descriptive ecological study - Silva de Oliveira, Francisco Eduardo; Carvalho Araújo Moreira, Andréa; Reis de Carvalho, Natalia; Teixeira Fernandes, Naiara; Vasconcelos Azevedo, Samir Gabriel; Monteiro da Silva, Maria Adelane (O Mundo da Saúde, 2022)
Studies that evaluate Hospitalizations due to Primary Care-sensitive Conditions (HPCSC) are relevant in the field of health, as they refer to indicators of hospital care that represent an indirect measurement of the effect of Primary Health Care (PHC), based on the premise that good quality PHC prevents/reduces hospitalizations among the elderly population. This article aimed to describe the behavior of HPCSC in elderly people aged 60 to 74 years old in the state of Ceará. This is a descriptive ecological study that analyzed the temporal evolution of annual rates of HPCSC in the elderly in the five health macro-regions of the state of Ceará, from 2008 to 2019. Secondary data regarding hospitalizations and the projection of the resident population for the calculation of rates were extracted, respectively, from the hospital information system and from the demographic database, both contained within the Tabnet of the Department of Informatics of the UHS. In the period from 2008 to 2019, there were 686,906 hospitalizations in the five health macro-regions of the state of Ceará, of which (298,002) were due to sensitive conditions. The highest rate of HPCSC (452.99) occurred in the Cariri macro-region. There was a predominance of elderly men (4,731) aged 70-74 years (5,893) and due to chronic conditions (2,195.3). There was a reduction in hospitalizations due to primary care-sensitive conditions in the period studied, except in the central Sertão region. The decrease in hospitalizations of the elderly in the state of Ceará may be related to a more resolute primary care in the care of the elderly.